Profiling of triacylglycerol composition in the breast milk of Chinese mothers at different lactation stages. Issue 18 (30th August 2022) - Lan, Qiu-Ye; Huang, Si-Yu; Jiang, Chen-Yu; Yang, Meng-Tao; Wu, Tong; Chen, Xiao-Yan; Liu, Zhao-Yan; Wei, Wei; Wang, Xing-Guo; Zhu, Hui-Lian
Abstract : Triacylglycerol (TAG) is the primary constituent of human milk fat and plays a vital role in the healthy development of infants. Abstract : Triacylglycerol (TAG) is the primary constituent of human milk fat and plays a vital role in the healthy development of infants. But few studies reported the sophisticated profile of TAG molecular species in human breast milk and its temporal changes during a prolonged lactation period. An efficient ultra-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF-MS) method was adopted to examine TAGs. A total of 128 TAGs in 296 human breast milk samples collected during postnatal 0 to 400 days were identified. The changes in the human milk TAG profile mainly took place in the early stages of lactation (postnatal 0–45 days), and the TAG profile became stable in mature milk after 200 days of lactation. Odd chain fatty acids (OC-FAs) may be important markers for identifying human breast milk of different lactation stages. This study could provide evidence for developing safe and efficacious human-milk substitutes for children without access to human breast milk.